Explaining the varied glycosidic conformational, G-tract length and sequence preferences for anti-parallel G-quadruplexes - Cang, Xiaohui (Oxford University Press, 2011)
Guanine-rich DNA sequences tend to form four-stranded G-quadruplex structures. Characteristic glycosidic conformational patterns along the G-strands, such as the 5′-syn-anti-syn-anti pattern observed with the Oxytricha nova telomeric G-quadruplexes, have been well documented. However, an explanation for these featured glycosidic patterns has not emerged. This work presents MD simulation and free energetic analyses for simplified two-quartet [d(GG)]4 models and suggests that the four base pair step patterns show quite different relative stabilities: syn-anti > anti-anti > anti-syn > syn-syn. This suggests the following rule: when folding, anti-parallel G-quadruplexes tend to maximize the number of syn-anti steps and avoid the unfavorable anti-syn and syn-syn steps. This rule is consistent with most of the anti-parallel G-quadruplex structures in the Protein Databank (PDB). Structural polymorphisms of G-quadruplexes relate to these glycosidic conformational patterns and the lengths of the G-tracts. The folding topologies of G2- and G4-tracts are not very polymorphic because each strand tends to populate the stable syn-anti repeat. G3-tracts, on the other hand, cannot present this repeating pattern on each G-tract. This leads to smaller energy differences between different geometries and helps explain the extreme structural polymorphism of the human telomeric G-quadruplexes.